Review of optimization techniques for scheduling school schedules - Montes Carvajalino, Daniel Alonzo; De la Hoz del Villar, Rita Cecilia; Del Rio Cortina, Jorge; Cardenas Escobar, Alba Zulay; Martinez Palomino, Oriana Susana (LACCEI, 2025)
The scheduling of timetables in school environments is one of the topics of greatest interest within the educational field, which is why a review of the techniques used for the scheduling of school timetables is presented, to identify them and compare some aspects that relate to them such as the quality of the solution, the execution time, the practical applicability and its limitations. For this purpose, current practices in creating school schedules are examined, as well as the tools and strategies used to improve efficiency and effectiveness in managing resources in educational institutions at various levels. The review initially addresses common challenges associated with school scheduling, including allocating limited resources, meeting the needs and preferences of students and teachers, and optimizing the distribution of teaching and learning time. The findings highlight that these techniques are valuable tools for educational management, which requires considering the specific constraints and limitations of each academic institution, in order to use the optimization technique that best suits the design and development of their school schedules